One foot in Eden : a novel - Rash, Ron, 1953- (Picador, 2004)
This brilliant southern gothic novel, by the award-winning and bestselling author Ron Rash, observes the consequences of love and murder across generations. Told from the perspective of the sheriff, a local farmer, his wife, their son and the sheriff's deputy, it explores the crime, shifting suspicion, blame and guilt with each new voice.